A In Vitro Callus Induction from (Antidesma bunius L.) Leaves - Adju, Fitria Y.Hs.; Ahmad, Jusna; pagalla, Devi Bunga; Kandowangko, Novri Youla; Husain, Indriati; Isima , Lindawaty (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2025)
Antidesma bunius L. is a tree species that has ecological and economic benefits, and has many bioactivities. Propagation of this tree can be done in several ways, one of which is callus induction. Callus is a collection of undifferentiated cells that can develop into new plants with the help of ZPT. The purpose of this study was to determine the effect and optimum combination of ZPT 2,4-D and BAP on the induction of leaf callus of A. bunius L. The research design was a non-factorial Completely Randomised Design (CRD) with 4 treatments namely P0: MS without the addition of zpt; P1: MS + 1 ppm BAP + 3 ppm 2,4-D; P2: MS + 2 ppm BAP + 2 ppm 2,4-D; P3: MS + 3 ppm BAP + 1 ppm 2,4-D. Parameters observed included callus emergence time, percentage of callus explants, and callus morphology. The results showed that P2 is the best concentration for callus induction, by looking at the observed effect on callus emergence time of 6 HST, percentage of callus explants 56% and callus morphology which is white with crumb texture, which can develop into embryogenic callus